Mediating effects of internal dynamics between parental attachment and delinquency among adolescents in Tehran, Iran - Manouchehri, Mahshid (2012)
Delinquency among adolescent is becoming an increasing concern in the Iranian society. The Iranian government has taken various steps in combating further increment of delinquent behaviours among adolescents. Numerous studies have investigated the underlying factors of adolescent delinquency. Nonetheless, very few research have focused on the essential role of maternal and paternal attachments on delinquency, particularly among Iranian adolescents. Hence, the present study aimed to examine whether maternal and paternal attachment and internal dynamics (i.e., self-control and self-esteem) simultaneously predict adolescents‟ delinquent behaviour. Additionally, the study examined the role of self-control and self esteem as mediators between the relationships of maternal and paternal attachment and adolescent delinquency. The study involved 528 adolescents (15 and 17 years old) from 10 government high schools in five selected districts in Tehran. The respondents were identified using multi-stage cluster sampling. Data were collected using self-administered questionnaires distributed during school hours. The instruments used to assess the key study variables were: 1) Delinquency scale, adapted from study by Harris et al.(2006); 2) Mother and Father Attachment Subscales of the Inventory of Parent and Peer Attachment (IPPA)(Armsden and Greenberg, 1987); 3) Self-esteem scale (Rosenberg, 1965); and 4) Self-control scale (Grasmick et al., 1993). Findings from the study revealed that: 1) High parental attachment scores were significantly related to low scores in delinquent activities among the Iranian adolescents. Secure paternal and maternal attachments could therefore dissuade adolescents to be involved in delinquent activities; 2) High parental attachment scores were significantly related to high scores in internal dynamics. Secure paternal and maternal attachments thus promote self-control and self esteem among the adolescents; 3) Low level of delinquency was negatively associated with internal dynamics. This tends to show that adolescents with lower levels of internal dynamics are more at risk of developing delinquent behaviours compared to those with higher levels; 4) Adolescents‟ age, fathers‟ years of education, maternal attachment and self control were found to be significant predictors of delinquency. The findings indicated that older adolescents with educated fathers, insecure maternal attachments and low level of self-control are more prone to engage in delinquency. Nonetheless, having low self-control tended to put adolescents at a higher risk of involving in delinquent activities; and, 5) The association between paternal attachment and delinquency was mediated by adolescents‟ self-control, i.e., paternal attachment indirectly influenced delinquency via self-control. Additionally unlike paternal attachment, the relationship between maternal attachment and delinquency was mediated by adolescents‟ self esteem. Maternal attachment therefore indirectly influenced delinquency via self esteem. The study highlights that in the Iranian society both maternal and paternal attachments are important for deterring adolescents involvement in delinquency. This strengthens past findings in which parents have a direct and indirect influence on the behavioural and social development of adolescents. Adolescents with insecure attachment relationships to both parents are more susceptible to poor development of internal dynamics and negative social behaviours. Therefore, parents are encouraged to be more attached to their adolescents in order to avert delinquent behaviours. Government and relevant agencies in Iran could develop programs that would educate parents to building and sustaining healthy relationships with their adolescents. The study emphasized the importance contribution of parents particularly, mothers in adolescent development. Future studies may wish to investigate the extent of paternal influence on adolescents‟ development, specifically with regards to internal dynamics and adolescent delinquency.